INCREASING GREEN BUSINESS LITERACY THROUGH ICT (INFORMATION AND COMMUNICATIONS TECHNOLOGY) FOR MSME BUSINESS PLAYERS - Ervani, Eva; Effendi, Nury; Indupurnahayu, Indupurnahayu; Intanie Dewi, Vera; Shinta Aminda, Renea; Samuel Sapulette, Militcyano (LPPM Univ. Ibn Khaldun Bogor, 2023)
Green business through ICT (Information and Communications Technology) is one way to make resources efficient. One example of the application of ICT in business is buying and selling that is done online or online business. The limited understanding of MSME business actors regarding the application of ICT in green business activities prompted the team of authors to carry out socialization by holding a training (workshop)